2017
DOI: 10.1155/2017/8764510
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and Microbiology of Sludge from a Thermophilic Aerobic Membrane Reactor

Abstract: A thermophilic aerobic membrane reactor (TAMR) treating high-strength COD liquid wastes was submitted to an integrated investigation, with the aim of characterizing the biomass and its rheological behaviour. These processes are still scarcely adopted, also because the knowledge of their biology as well as of the physical-chemical properties of the sludge needs to be improved. In this paper, samples of mixed liquor were taken from a TAMR and submitted to fluorescent in situ hybridization for the identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 88 publications
1
9
0
Order By: Relevance
“…subject of a publication by Abbà et al [33], despite the large time interval between the two measurements, we note the continued absence of nitrifying bacteria. Figure 6 The biomass of this plant proves to be quite peculiar, given the particular process conditions that lead to the development of minute flocs and a bacterial community whose populations are present in different percentages compared to conventional activated sludge.…”
Section: Biota Characteristicssupporting
confidence: 52%
See 1 more Smart Citation
“…subject of a publication by Abbà et al [33], despite the large time interval between the two measurements, we note the continued absence of nitrifying bacteria. Figure 6 The biomass of this plant proves to be quite peculiar, given the particular process conditions that lead to the development of minute flocs and a bacterial community whose populations are present in different percentages compared to conventional activated sludge.…”
Section: Biota Characteristicssupporting
confidence: 52%
“…In any case, no AOB (Ammonia Oxidizing Bacteria), NOB (Nitrite Oxidizing Bacteria), and anammox bacteria were identified. If we compare the results with the results of the analysis carried out on samples from the same AWTP plant, which was the subject of a publication by Abbà et al [33], despite the large time interval between the two measurements, we note the continued absence of nitrifying bacteria. Figure 6 displays a picture of the flocs, which have a diameter always lower than 150 µm and are quite dense, without any bone of filaments, as previously highlighted.…”
Section: Biota Characteristicsmentioning
confidence: 84%
“…The study showed that the apparent viscosity, the yield stress and the fluid consistency increased with the TS concentration increase [76]. Abbà et al (2017) evaluated the rheology and microbiology of sludge from a thermophilic aerobic membrane reactor [77]. The Hershel-Bulkley model fitted with experimental data [77].…”
Section: Impact Of the Sludge Age On The Rheological Behaviormentioning
confidence: 99%
“…Testing a secondary sludge, they found that both the threshold stress and the plastic viscosity were positive correlated with pH increases up to 7, highlighting that the best cohesion of the flocs and occurred in acidic conditions with pH between 6 and 7 (Dollet & Baudu 2000). Abbà et al (2017) and Collivignarelli et al (2019c) studied the effect of TSS content on rheological behaviour showing that the sludge derived from a Thermophilic Aerobic Membrane Reactor (TAMR), with 150 g TSS /L exhibited shear-thickening (dilatant) behaviour. When TSS increase up to 190 g/L, the interactions between the sludge particles were expected to be even more intense and therefore a non-zero yield stress was observed.…”
Section: Influence Of Physical Chemical Parametersmentioning
confidence: 99%
“…Moreover, the thermally treated sludge exhibited gel-like, viscoelastic characteristics similar to untreated sludge (Hii et al 2017). Abbà et al (2017) studied the rheological properties of the sludge derived from a Thermophilic Aerobic Treatment Reactor (TAMR), that is an innovative membrane bioreactor (MBR) treatment that works around 50 °C. Also in this case, the most important parameter that affect the rheological behaviour is the TSS concentrations (in this case up to 200 g/L).…”
Section: Influence Of the Type Of Treatmentmentioning
confidence: 99%